Mindfulness and mental preparation - Fournier, J. (Advances in mental skills training, 2021)
Mindfulness has received a lot of attention in recent years. Evidence suggests that mindfulness is useful for improving performance because it can help maintain focus in problem situations (Gardner & Moore, 2012; Mardon, Richards, & Martindale, 2016) which does not detract from the more general use of mindfulness in the pursuit of wellbeing. In this chapter, we first review the literature related to the use of mindfulness for improving performance in sport and then present a program of intervention implemented in a case study with an elite fencer.